TRPV6 is not required for 1α,25-dihydroxyvitamin D(3)-induced intestinal calcium absorption in vivo - Kutuzova, Galina D. (National Academy of Sciences, 2008)
The requirement for TRPV6 for vitamin D-dependent intestinal calcium absorption in vivo has been examined by using vitamin D-deficient TRPV6 null mice and littermate wild-type mice. Each of the vitamin D-deficient animals received each day for 4 days 50 ng of 1,25-dihydroyvitamin D(3) in 0.1 ml of 95% propylene glycol:5% ethanol vehicle or vehicle only. Both the wild-type and TRPV6 null mice responded equally well to 1,25-dihydroxyvitamin D(3) in increasing intestinal calcium absorption. These results, along with our microarray data, demonstrate that TRPV6 is not required for vitamin D-induced intestinal calcium absorption and may not carry out a significant role in this process. These and previous results using calbindin D9k null mutant mice illustrate that molecular events in the intestinal calcium absorption process in response to the active form of vitamin D remain to be defined.